The operational mechanism of ferroelectric-driven organic resistive switches - Kemerink, Martijn; Asadi, Kamal; Blom, P. W. M.; Leeuw, Dago M. de (Organic electronics, 2012)
The availability of a reliable memory element is crucial for the fabrication of ‘plastic’ logic circuits. We use numerical simulations to show that the switching mechanism of ferroelectric-driven organic resistive switches is the stray field of the polarized ferroelectric phase. The stray field modulates the charge injection from a metallic electrode into the organic semiconductor, switching the diode from injection limited to space charge limited. The modeling rationalizes the previously observed exponential dependence of the on/off ratio on injection barrier height. We find a lower limit of about 50nm for the feature size that can be used in a crossbar array, translating into a rewritable memory with an information density of the order of 1Gb/cm2.
Available online 7 November 2011
Gesehen am 04.12.2019